2021
DOI: 10.1088/1361-6463/ac2d60
|View full text |Cite
|
Sign up to set email alerts
|

A strategic review of recent progress, prospects and challenges of MoS2-based photodetectors

Abstract: Two-dimensional layered materials have emerged prominently in the past decade, largely being investigated fundamentally and practically. Their unique layered structure and atomic-scale thickness make them attractive with exclusive electrical and optical properties compared to their bulk counterparts. Molybdenum disulfide (MoS2) is the most widely studied material in the family of transition metal dichalcogenides. The direct and variable bandgap, high carrier mobility, thermal and chemical stability makes it an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 245 publications
0
40
0
Order By: Relevance
“…The net effect is that our devices show superlative performance with competitive response times and over three orders of magnitude higher responsivity than previously reported all-printed photodetectors in the visible light spectrum (Figure 4f; Table S2, Supporting Information). [22][23][24][26][27][28][29]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The net effect is that our devices show superlative performance with competitive response times and over three orders of magnitude higher responsivity than previously reported all-printed photodetectors in the visible light spectrum (Figure 4f; Table S2, Supporting Information). [22][23][24][26][27][28][29]…”
Section: Resultsmentioning
confidence: 99%
“…A tradeoff between responsivity and time response is observed, where a long lifetime of trapped charges increases photocurrent gain but also slows down the temporal response. [ 27 ] While the fastest response time yields a responsivity of 1.8 × 10 3 A W −1 with a response time of ≈1–2 ms, the maximum responsivity obtained was 8.6 × 10 3 A W −1 with a response time of ≈3 s (Figure 4f). Our all‐printed photodetectors exhibit relatively fast response times compared to some examples of ≈1 s timescales reported for CVD‐grown and mechanically exfoliated MoS 2 photodetectors with comparatively high responsivities.…”
Section: Resultsmentioning
confidence: 99%
“…13 No doubt, 2D materials exhibit excellent optical and electronic properties, which enhance the parameters of photodetectors in comparison to other materials, but the problem is the complexity of fabricating these devices. [14][15][16] In the current scenario, polymeric-inorganic nanohybrid type metallopolymers/MOFs materials have been adopted for nextgeneration devices because of the advanced properties generated by the conjugation of polymeric and inorganic hybrid materials. [17][18][19] Xianguang Yang et al reported the broadband photodetector based on the CdSe-ZnS core-shell type materials incorporated in the polyaniline nanowire exhibited R l and EQE of 10 5 A W À1 and 10 6 , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The exploration of novel semiconductors with favorable electronic and optical properties 1,2 is essential for the development of advanced optoelectronic devices, such as field effect transistors (FETs), 3 photodetectors, 4 phototransistors, 5 solar cells, 6 photovoltaics, 7 memory devices, 8 gas sensors, 9,10 fiber lasers 11 and photocatalysts. 7 In recent years, two-dimensional (2D) materials have attracted the attention of many researchers, because of their rich physics and potential electronic and optoelectronic applications.…”
Section: Introductionmentioning
confidence: 99%